Apathy in Alzheimer’s Disease Correlates with the Dopamine Transporter Level in the Caudate Nuclei - Niki Udo; Naoki Hashimoto; Takuya Toyonaga; Tomoyuki Isoyama; Yuka Oyanagi; Hisashi Narita; Tohru Shiga; Shin Nakagawa; Ichiro Kusumi (Dementia and Geriatric Cognitive Disorders Extra, 2020)
Introduction: Apathy is a common neuropsychiatric symptom in patients with Alzheimer’s disease (AD). The striatal binding potential (BP) of 123I-FP-CIT (N-δ-fluoropropyl-2β-carbomethoxy-3β-[4-iodophenyl]tropane) single-photon emission computed tomography (SPECT) is correlated with the degree of apathy in patients with Parkinson’s disease (PD) and dementia with Lewy bodies (DLB). This study aimed to determine if dopaminergic activity in the basal ganglia is associated with the development of apathy in AD. Methods: Nineteen subjects with AD were included and underwent 123I-FP-CIT-SPECT. Patients with other types of dementia as a comorbidity, those taking antidepressants, and those with overt parkinsonism were excluded. Apathy was assessed using the Apathy Evaluation Scale Informant-Japanese version (AES-I-J). SPECT images were overlaid with images in striatal regions of interest (ROIs), and the SPECT values in these regions were counted. The relationship between BP values and AES-I-J scores was investigated using Spearman’s rank correlation coefficient. Results: Significant inverse correlations were observed between BP values and AES-I-J scores in the left caudate nucleus and there was a marginally significant inverse correlation in the right caudate nucleus. Conclusion: The pathological basis of apathy might be the impairment of the dopaminergic nervous system. Further studies on more subjects with AD, healthy controls, and patients with PD and DLB are needed.